2005
DOI: 10.1002/pbc.20645
|View full text |Cite
|
Sign up to set email alerts
|

Early blood transfusions protect against microalbuminuria in children with sickle cell disease

Abstract: We conclude that: (1) children with sickle cell hemoglobinopathies 10 years or older should be screened for MA and (2) chronic transfusions starting at an early age may be renoprotective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
86
3
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 21 publications
14
86
3
4
Order By: Relevance
“…35 Two further studies, however, found that chronic transfusion made no difference to the onset of proteinuria. 36,37 Although it seems logical that chronic transfusion could be effective at preventing many of the renal complications of SCD, this therapy is not a minor undertaking, and evidence of its benefits is needed before it can be justified for the treatment or prevention of SCN.…”
Section: Other Preventative or Early Treatment Options Red Cell Transmentioning
confidence: 95%
“…35 Two further studies, however, found that chronic transfusion made no difference to the onset of proteinuria. 36,37 Although it seems logical that chronic transfusion could be effective at preventing many of the renal complications of SCD, this therapy is not a minor undertaking, and evidence of its benefits is needed before it can be justified for the treatment or prevention of SCN.…”
Section: Other Preventative or Early Treatment Options Red Cell Transmentioning
confidence: 95%
“…In a cross-sectional study of 410 patients with SCD aged 2-21 (mean age 11) years, 23% had the HbSS form of SCD, with elevated urinary albumin excretion (≥30 mg/g), while other investigators have reported a HbSS prevalence of 16-27% in the childhood SCD population [18,20,21]. Further progressive kidney injury and CKD is reflected in a declining and abnormally low GFR.…”
Section: Sickle Cell Nephropathy In Childrenmentioning
confidence: 99%
“…In one study a urinary screening of asymptomatic SCD patients revealed microalbuminuria in 15.8% of patients [7]. Another study indicated that 22.3% of SCD patients had microalbuminuria [8].…”
Section: Discussionmentioning
confidence: 99%
“…40% of causes of mortality among adult SCD patients were due to renal failure [6]. Several published studies identified microalbuminuria and proteinuria as major renal manifestations among adult SCD patients [7] [8]. In this study, we focused on renal manifestations of adult Sudanese patients with SCD.…”
mentioning
confidence: 99%